Forming of Communicative Skills of the Future Agrarians in the Sphere of Reading in the Process of Educational Disciplines’ Integration in Higher Educational Establishments - Dziubata, Zoryana (Pedagogical Discourse, 2013)
The article investigates the ways of solving the problem of the effective and systematic forming of communicative skills of the future agrarians in the sphere of reading, under the conditions of limited academic hours provided for this purpose by means of the integration based on the methods of teaching Humanities in agrarian higher educational establishments, namely to the substantiation of the peculiarities of agrarians’ reading process for specific purposes; analyzing the ways of forming such skills in the process of integrating Humanities for that purpose; to working out the effective structure of reading activity and special exercises in order to form communicative agrarians’ reading skills.